Pregnancy outcomes in patients with rheumatoid arthritis and systemic lupus erythematosus. Part I. Maternal outcomes - N. M. Kosheleva; E. V. Matyanova; E. V. Fedorova; N. I. Klimenchenko (Научно-практическая ревматология)
Improved diagnosis and treatment of rheumatoid arthritis (RA) and systemic lupus erythematosus (SLE) contribute to the remission of the disease and improve the quality of life of patients. In this regard, more and more women with RA and SLE decide to have pregnancy, which makes it actual to study the features of its course and outcomes in these diseases.Objective: to evaluate maternal pregnancy outcomes in patients with RA and SLE.Subjects and methods. 76 cases of pregnancy were traced prospectively in 72 patients: 32 pregnancies in 29 patients with RA and 44 pregnancies in 43 patients with SLE.Results and discussion. 72 of 76 (94.7%) supervised pregnancies ended in childbirth with the birth of a viable baby. There were three cases of pregnancy loss in the second trimester in SLE patients with concomitant antiphospholipid syndrome (AFS) and one case (3.1%) of perinatal infant death (a boy and a girl, monochorionic diamniotic twins with reverse arterial perfusion syndrome) in a patient with seropositive RA. Compared with the all-Russian population, the supervised RA and SLE patients more often had prematurely birth (37.5‰, 18.7% and 22.7%) and caesarean section (CS; in 236.7‰, 50%, and 56.8% respectively). In the SLE group CS was conducted due to the emergency reasons more frequently than in RA, (respectively 47,7% and 25%, relative risk of 1.9 [1; 3.7]; p=0.04). CS at the first birth was performed more often during RA and SLE than before the onset of the disease (p<0.001). Preeclampsia in patients with RA was diagnosed more often than in the population (9.4% and 15.7 per 1000 births, respectively). There was a reverse correlation between the timing of delivery and disease activity according DAS28-CRP in II (r= 0.5; p=0.01) and III (r= 0.6; p=0.0005) trimesters of pregnancy, and in patients with moderate and high activity of RA in the third trimester (n=12) delivery was earlier than in the control group (n=20), remission or low activity of RA (p<0.01). In patients with SLE who had birth prematurely (22.7%), the duration of the disease (p=0.02) and the duration of oral glucocorticoid therapy (p=0.003) were greater compared with SLE patients having term birth (70.5%); the dose of glucocorticoids at the time of conception and delivery did not affect the timing of delivery.Conclusion. Planning of pregnancy in patients with RA and SLE, monitoring during pregnancy and timely correction of therapy contribute to uncomplicated course of gestation and improve maternal outcomes.